Consumer Confidence and Consumer Spending in Brazil: A Nonlinear Autoregressive Distributed Lag Model Analysis - Ghosh, Sudeshna (Arthaniti (2002), 2021)
The study explores the relationship between consumer confidence, household private consumer expenditure and other related macroeconomic financial variables for Brazil, a major, upper middle, income, Latin American country. It is widely discussed in the literature that the consumer confidence is an initial guide to the future behaviour of the economy based on the consumption path. Thus, a rise in the confidence of the consumer would lead to rising household consumption behaviour, which would percolate to accelerate economic growth. The study uses the nonlinear autoregressive distributed lag model (NARDL) to measure the effects of changes in consumer sentiment on private consumer spending, taking into consideration the significance of other financial variables, namely the rate of interest, stock market index, the exchange rate, inflation and unemployment trends. The study employs monthly data from the 4th month of 1995 to the 10th month of 2018. The bounds test of the NARDL suggests the presence of a cointegrating relationship among the variables. The model estimation affirms the presence of asymmetries in the behaviour of the major explanatory variables. In the short run, there are both positive and negative asymmetric impacts of consumer confidence index (CCI) on consumer expenditure, while the rate of interest has only negative asymmetries. In the long run, unemployment changes, stock market fluctuations, interest rate variation and alterations in the CCI shape the behaviour of consumer spending at the household level in Brazil. So, the consumers are able to perceive the signalling of the future behaviour of the market and contribute through consumption spending. JEL: C22, D12, E21, O54